A non-randomized prospective study of the blood sparing effect of tranexamic acid in total knee replacement - Gupta, Anand; Nagla, Ashok; Tantuway, Vinay; Gupta, Rishi; Patel, Vivek; Bhambani, Pawan (International Journal of Research in Orthopaedics, 2016)
Background: Several techniques are available to minimize the likelihood of blood transfusion following total knee arthroplasty. Tranexamic acid, an inhibitor of fibrinolysis that blocks the lysine-binding site of plasminogen to fibrin has been reported to reduce intraoperative and postoperative blood loss in patients undergoing total hip and total knee arthroplasties with or without cement. The objective of this study was to assess the efficacy of antifibrinolytic treatment along with other measures like saline adrenaline infusion, no drain, no tourniquet and hypotensive anaesthesia in reducing perioperative blood loss during total knee replacement. Methods: Between January 2011 to January 2016, seventy five consecutive patients who had given written informed consent, undergoing a TKR received tranexamic acid 15 mg/kg body weight intravenous 5 minutes before the skin incision and two doses afterwards (3 and 6 hours after the first dose respectively). TKR was performed in a routine fashion without tourniquet. The saline adrenaline (1:200000) was infiltrated into the skin subcutaneous tissue and capsule before skin incision. A routine closure was carried out without drain. Total blood loss including the hidden blood loss was calculated. All patients were monitored for anemia and postoperative thromboembolic complications. Results: The average total blood loss in study group is 433 ± 148 ml. This is much lesser than what other studies have reported. Mean reduction in hemoglobin levels (gm/dl) between preoperative and postoperative readings is 1.6 gm/dl. One patient had a postoperative DVT which was treated with rivaroxaban 20 mg OD for 6 weeks (oral anticoagulant). Conclusions: Antifibrinolytic agents like tranexamic acid used along with other measures reported in this study produces a significant decrease in blood loss in patients undergoing total knee replacement.